Human Capital Management in Achieving Excellent Accreditation: A Study of an Islamic Higher Education - Rony Edward Utama; Fathurachman; Andry Priharta; Nur Asni Gani; Jaharuddin; Yahaya Niwae (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
This research highlighted two objectives, namely: (1) how Universitas Muhammadiyah Jakarta managed its human capital in relation to its vision, missions, and goals as an Islamic university; (2) strategic plans employed by this university and key performance of its human resources to fulfill the implementation of human capital management in the efforts of achieving excellent accreditation. This study was carried out in the academic year of 2023/2024 at Universitas Muhammadiyah Jakarta. The method employed was qualitative using study case research design. The instruments used in data collection were observation, document study, and non-formal interviews. The data were analyzed based on human capital management’s model of Mayo (2000) covering five elements, i.e., individual capability, individual motivation, leadership, the organizational climate, and work-group effectiveness. The analysis data revealed that: 1) in managing its human capital, the university carried out five work stages, they are the stages of preparation, implementation, monitoring and evaluation, control and improved which of all stages met the five aspects of Mayo’s HCM model. Second, both strategic plans and key performance for its human resources were well-planned, designed, and managed by the institution, hence the target of achieving excellent accreditation was successfully achieved.